Measurement of actual evapotranspiration in a páramo ecosystem using portable closed chambers: Comparison between giant rosettes, tussock grasses and shrubs - Meyers, Barbara; Gutiérrez‐Lagoueyte, María Elena; Tobón, Conrado (Ecohydrology, 2023)
Abstract The páramos are Neotropical alpine tundra‐like ecosystems that play a crucial role as biodiversity hotspots and also act as water sources for the inter‐Andean regions and cities. Improving our understanding of hydrological processes, here evapotranspiration, is crucial, especially in the context of global changes. In páramos, most research have focused on estimating potential evapotranspiration (ETo) using the Penman–Monteith method. Only a few studies have quantified actual evapotranspiration using mostly the Eddy covariance method (EC) or volumetric lysimeters. Importantly, these studies focused only on tussock grass communities, and none have addressed the effect of other plant communities specific to páramos on the actual evapotranspiration of this ecosystem. In this research, portable closed chambers were installed for the first time in a páramo (in Los Nevados National Park, between 3900 and 4100 masl) to quantify actual evapotranspration (ETa) in March and May 2019 in three representative plant communities of the páramo (giant rosettes, shrubs and tussock grasses). The ETa rates measured were then compared with ETo estimated using the Penman–Monteith method. Also, environmental factors of solar radiation, temperature and relative humidity were recorded and their influence on ETa variation was analysed. Our results indicate that ETa daily rates were very low with a high daily variation (0.290 ± 0.266 mm day −1 ). The shrubs showed higher ETa rates even though differences among communities were not significant. ETo rates calculated via the Penman–Monteith method were significantly higher (1.017 ± 0.468 mm day −1 ) than those measured using the portable chambers. Portable closed chamber is a promising method to assess ETa at small spatial and time scales and under controlled environment; however, they should be improved to enable ETa measurements on longer time periods. This study confirms the highly variable and low evapotranspiration rate of the páramo vegetation, here confirmed across different ...